Physicochemical properties of lipase‐catalyzed laurylation of corn starch. Issue 5 (4th November 2013) - Gao, Yan; Wang, Lan; Yue, Xiali; Xiong, Guangquan; Wu, Wenjin; Qiao, Yu; Liao, Li
<x xml:space="preserve">Abstract</x> Corn starch was esterified with lauric acid by using lipase as catalyst in low moisture. The physicochemical and granular properties of esterified starches were determined, including transmittance, syneresis, swelling power, solubility, and thermal analysis, as well as SEM and XRD analysis. The amylose content of esterified starches was in the range of 47.31–48.69%, corresponding with the degree of substitution (DS) ranging from 0.0033 to 0.0151. There was a significant increase in syneresis, swelling power, solubility, and gelatinization temperature, but a decrease in transmittance of esterified starches. The results of SEM and XRD analysis revealed that esterification led to apophyses and pores on the surface of starch granules, but caused few changes in the crystalline structure of esterified starch (DS = 0.0109, 0.0151). Thermal gravimetric analysis (TG) indicated that the esterified starch showed thermal instability compared with native starch.